Inclusive Workplace: A Conceptual Study of Workers with Disabilities - Syahrina Hayati Md Jani; Siti Nurul Akmax Siti Nurul Akma Ahmad; Siti Mariam Ali; Nortasik Misba (Information Management and Business Review, 2025)
This article explores the challenges and opportunities associated with creating an inclusive workplace for workers with disabilities.  Besides, it examines key barriers, such as physical and technological accessibility, organizational culture, and leadership attitudes, while also identifying opportunities for positive change through inclusive practices, policies, and innovation. The study aims to provide a comprehensive understanding of the factors influencing the inclusion of workers with disabilities and offer actionable insights for organizations seeking to foster a more inclusive environment.